Shortage of plasma-derived medicinal products: what is next? narrative literature review on its causes and counteracting policies in Italy - Bolcato, Matteo; Jommi, Claudio (Frontiers in Pharmacology, 2024)
Introduction: This paper describes the peculiarities of the plasma-derived medicinal product (PDMP) market and illustrates the results of a review of the literature on policies aimed at counteracting the shortage of PDMPs. Characteristics of PDMPs: Plasma is primarily used for the industrial production of blood products (80%). The demand for PDMPs, particularly immunoglobulins (IGs), is increasing. However, the production of PDMPs is complex, long (7-12 months), and expensive, accounting, according to US estimates, for 57% of the total costs of PDMPs compared to 14% for small molecules. PDMP market: Unexpected increases in clinical need cannot be addressed in the short term. Once the demand for some diseases is satisfied, the collection and fractionation of plasma will only be used to supply some specific patients. Hence, the full weight of the marginal costs, which remain constant, are borne by a few products. According to last liter economics, the industry stops producing when the marginal revenue equals the marginal cost, thereby reducing the convenience of producing the most commonly used PDMPs (albumin and IG). The imbalance between the demand and supply of PDMPs was exacerbated by the Covid-19 pandemic, which further increased the cost of plasma collection. Shortage issue and possible solutions: Policies to counteract this imbalance have also been discussed. If the demand is inappropriate, it should be reduced. If the demand is appropriate and supply cannot be increased, the demand should be prioritized for patients for whom PDMPs are the only available treatment. If the shortage depends on insufficient supply and technical and allocative efficiency, both production and supply should be improved, together with incentives for all stakeholders involved in the PDMP market to increase the sustainability of production/supply. Through a literature review, this study explores the peculiarities of the PDMP market and policies aimed at managing the shortage of PDMPs. This important topic has been discussed in various reports, but not through an updated review, and without a holistic approach. Policies should address specific problems, investigate the causes of shortages, and implement the appropriate policies to mitigate the challenges.